Recent Insurance and Takaful Coverage for Diabetics in Malaysia:A Review - Seman, Junaidah Abu; Kamarubahrin, Aimi Fadzirul; Mirza, Azrul Azlan Iskandar; Muhamed, Nurul Aini; Zulkefli, Zurina Kefeli; Rashid, Mohd Radzniwan A; Muhamad, Sharifah Fairuz Syed; Ahmad, Saharuddin (The journal of contemporary issues in business and government, 2022)
This paper reviews the recent insurance and takaful coverage for diabetics in Malaysia. Also, this study reported insurance and takaful operators offer diabetes plan available in the market. A comprehensive review of the insurance and takaful literature was conducted and content comparisons based on research focus dan context were evaluated. It was found that only three insurance companies in Malaysia offer protection plans for diabetics while no takaful operator offers the coverage. Diabetes protection plan for the low-income group is proposed to be covered under the micro-insurance or micro-takaful, with a sum covered between RM10,000 to RM100,000 and low monthly contribution. Furthermore, as this paper concentrates on insurance and takaful coverage for diabetes protection in Malaysia, the possibility that other relevant works do appear elsewhere in a different platform is not denied. The paper will be useful to researchers, professionals and others concerned with micro-insurance or micro-takaful products to understand the importance of diabetes plan. Other than revealing ambiguities, gaps and contradictions in the literature, this paper provides information and guidance for other researchers wishing to embark on research on insurance and takaful diabetes coverage protection.